KONTRIBUSI PANJANG LENGAN, KEKUATAN OTOT LENGAN DAN KOORDINASI MATA-TANGAN TERHADAP KEMAMPUAN SERVIS BAWAH BOLA VOLI PADA SISWA SMA GARUDA KOTABARU - Muhammad Imran Hasanuddin (STKIP Paris Barantai, 2019)
This research is a type of descriptive research. This study aims to determine: (1) Is there an arm's length contribution to the ability to serve under the volleyball of Garuda Kotabaru High School students. (2) Is there any contribution of arm muscle strength to the volleyball service of Garuda Kotabaru High School students, (3) Is there a contribution of eye-hand coordination to the volleyball service ability of Garuda Kotabaru High School students, (4) Is there a contribution to arm length, strength arm muscles and eye-hand coordination of the ability to serve under the volleyball of Garuda Kotabaru High School students. The population is all Garuda Kotabaru high school students. The sample used was Garuda Kotabaru high school students as many as 35 people. The technique of determining the sample is by random selection by lottery (Simple Random Sampling). The data analysis technique used is descriptive analysis and inferential analysis through the SPSS 22 program at a significance level of Î± 0.05. The results showed that; (1) Is there a contribution of arm length to the service ability under volleyball of Garuda Kotabaru High School students, amounting to 31.0%., (2) Is there a contribution of arm muscle strength to the service of under volleyball of Garuda Kotabaru High School students, by 31.5%, (3) Is there a contribution of eye-hand coordination to the volleyball service abilities of Garuda Kotabaru high school students, by 25.9%, (4) there is a contribution of arm length, arm muscle strength and eye-hand coordination to the ability to serve under volleyball for Garuda Kotabaru high school students by 57.7% with F: 13.999 and sig (p) = 0,000. Keywords: Arm length, arm strength, hand-eye coordination and Volleyball serve